Rethinking antimicrobial stewardship paradigms in the context of the gut microbiome. Issue 1 (21st May 2019) - Shahi, Farah; Redeker, Kelly; Chong, James
Abstract: Ongoing concerns over the presence and persistence of antimicrobial resistance (AMR), particularly in Gram-negative bacteria, continue to have significant global health impacts. The gastrointestinal tract, or 'gut', environment amplifies AMR in the human gut microbiome, even in the absence of antibiotics. It constitutes a complex and diverse community of organisms, and patterns and alterations within it are increasingly being found to be associated with states of health and disease. Our understanding of the effects of routes of administration of antimicrobials on the gut microbiome is still lacking despite recent advances in metagenomics. In this article we review current evidence for antibiotic effects on gut microbiota and explore possible prescribing and stewardship approaches that would seek to minimize these effects. If we are to preserve existing and new antimicrobials, we need to consider their use in the context of their effect on gut ecology, and the human microbiome in general.